Formulations And Evaluation Of Herbal Shampoo And Comparative Studies With Herbal Marketed Shampoo. - SWATI DESHMUKH,; BINDURANI KAUSHAL,; SHWETA GHODE, (International Journal of Pharma and Bio Sciences, 2012)
A shampoo is a cleaning aid for the hair and is counted among the foremost beauty products. Today’s shampoo formulations are beyond the stage of pure cleaning of the hair. Additional benefits are expected, e.g., conditioning, smoothing of the hair surface, good health of hair, i.e., hair free of dandruff, dirt, grease and lice and, above all, its safety benefits are expected. In the present scenario, it seems improbable that herbal shampoo, although better in performance and safer than the synthetic ones, will be popular with the consumers. We have evaluated the formulation, and compared the herbal shampoo, with a marketed shampoo. We have used the physic-chemical approach to preservation and by formulating a self preserving shampoo, have avoided this risk posed by chemical preservatives. However, the aesthetic attributes, such as lather and clarity, of the laboratory shampoo are not comparable with the marketed shampoo. The foam volume was on a par. It is very important to know and understand effects of ingredients used in shampoo formulations. In the present study the shampoos based on synthetic ingredients and herbal ingredients are compared for their effectiveness and safety.